Comparison of General Health and Depression in the People Covered With the Community-Based Rehabilitation Program (CBR) With the Non-Covered - Karim Ayoubi Avaz; Omid Hashemi; Saman Karami; Mehdi Rassafiani; Roghaie Hatami (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective The prevalence of disability is growing with the development of science and industrialization of the society. Disability is a psychological, biological phenomenon and impairment in any of these areas affect a person's health. Similar to other people in the community, these people need to use similar services. One of the critical issues for these people is the use of rehabilitation services. Rehabilitation services can be effective in improving the physical and mental status of people with disabilities. In some developing countries, there are no rehabilitation services, and only some services are provided in institutions and few needy people can use it. Community-Based Rehabilitation (CBR) encompasses a large part of the needs of people with disabilities including activities of daily living, social activities, and empowerment. CBR provide the essential rehabilitation services for the people living in remote and impoverished areas. The CBR program provides health and quality of life services which can increase individual’s ability and prevent factors such as depression and dependence due to disability. Considering that the evaluation of each plan and program is in the tasks and responsibilities of the management and that the CBR program is running since 2007 in the city of Bostanabad; however, its effectiveness has not been studied. Literature is scarce on the effectiveness of CBR programs among the two covered and non-covered groups. It is necessary to examine the effectiveness of CBR programs in improving the mental health status of the persons with disabilities. The aim of this study was to compare general health and depression of the people covered by the CBR program with non-covered. Materials & Methods This was a cross-sectional study. Physical movements impaired people qualified for the inclusion in the villages covered by CBR (n=48) in Bostanabad, and not under the CBR service (n=45, control group) in other villages were enrolled for this study. All participants in this study completed three questionnaires, including demographic, General Health Questionnaire (GHQ28) and Beck Depression Inventory (BDI-II). Data were analyzed using t-test independent for comparative groups. Results according to the results, 57% of participants were male, and 51.6% had a mild disability. The results do not demonstrate a significant difference in General Health between the two groups (P=0.870). GHQ28 subscales demonstrated a significant difference in depression (P=0.001) and social impairment (P=0.001) between two groups. There was no significant difference in the subscales of physical symptoms (P<102.9) and the symptoms of anxiety and sleep disorders (P<0.331). Participants in the CBR program demonstrated a lower level of depression compared with the non-covered group Conclusion  Implementing the CBR programs in rural and remote areas can be effective in reducing the depression of people with physical disabilities. These programs can create meaningful change and a more comprehensive framework for people with physical disabilities and can have positive effects on the general health. Further studies are required to collect more data about the general health and the quality of life of these groups of patients.